Blended learning in higher education for the development of intrinsic motivation: a systematic review - Rebeca Kerstin Alonso; Alexander Velez; María Ángeles Diego Mantecón; Esther Heredia Oliva (Cogent Education)
As part of emerging educational trends, blended learning is regarded as an effective instructional approach for classroom use that is posited to help enhance intrinsic motivation, an important element which is critical for quality education. During the past ten years, blended learning has been increasingly implemented in higher education, and searches for possible interventions have consequently grown. Nevertheless, there are currently no published reviews that examine the effects of blended learning interventions on intrinsic motivation. Thus, the goals of this paper were to examine the connection between students’ intrinsic motivation and blended learning usage in higher education and to pinpoint the elements of blended learning models that should be included in order to develop intrinsic motivation and support high-quality instruction. A systematic review was conducted in compliance with PRISMA guidelines. Of the 553 papers that were originally found, 15 were thoroughly examined and analyzed. Most of the blended learning interventions improved intrinsic motivation outcomes after being implemented in very diverse areas of knowledge. In conclusion, five crucial elements were found that need to be adhered to in the blended learning methodology to intrinsically encourage students.